2011
DOI: 10.1111/j.1748-0361.2011.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

A National Study of the Association Between Food Environments and County-Level Health Outcomes

Abstract: The food access/availability environment is an important determinant of health outcomes in metro and non-metro areas. Future research should focus on more refined specifications that capture variability across non-metro settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 75 publications
(81 reference statements)
8
115
1
1
Order By: Relevance
“…26 If we assume that the effect of fast food on weight gain for pregnant mothers is the same as for nonpregnant women (an admittedly strong assumption that is likely to give an upper bound estimate), then fast food restaurants near a woman's 25 According to our measure, about 33 percent of ninth graders in California were obese during the 1999-2007 period. Since obesity among adolescents (age [12][13][14][15][16][17][18][19] approximately tripled from 1970 to the late 1990s, we estimate the increase in obesity of ninth graders in the past 30 years to be about 22 percentage points. Hence, we compute the effect as 1.7 percentage points (the estimated impact of fast food on obesity at 0.1 miles) multiplied by 0.067 (the share of schools at 0.1 miles in 1999-2007, assumed to be zero in the 1960s) divided by 22 percentage points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 If we assume that the effect of fast food on weight gain for pregnant mothers is the same as for nonpregnant women (an admittedly strong assumption that is likely to give an upper bound estimate), then fast food restaurants near a woman's 25 According to our measure, about 33 percent of ninth graders in California were obese during the 1999-2007 period. Since obesity among adolescents (age [12][13][14][15][16][17][18][19] approximately tripled from 1970 to the late 1990s, we estimate the increase in obesity of ninth graders in the past 30 years to be about 22 percentage points. Hence, we compute the effect as 1.7 percentage points (the estimated impact of fast food on obesity at 0.1 miles) multiplied by 0.067 (the share of schools at 0.1 miles in 1999-2007, assumed to be zero in the 1960s) divided by 22 percentage points.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Centers for Disease Control and Prevention (CDC) 2000 growth charts, it only takes a weight gain of 3.6 pounds to move from the eightieth to the eighty-fifth percentile of the BMI distribution. Over a period of 30 weeks, 16 this corresponds to a gain of about 80 additional calories per school day. It would take 300 additional calories to move from the nintieth to the ninety-fifth percentile of BMI, where the later is the cutoff for obesity.…”
Section: B Magnitude Of the Estimated Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Las peores condiciones registradas en el área urbana, especialmente por la carga de la malnutrición por exceso, puede ser entendida en el contexto de la transición nutricional, dado que estas zonas presentan mayor disponibilidad y oferta de alimentos industrializados y locales de comidas rápidas (Ahern, Brown y Dukas, 2011). En el caso de Yerba Buena, los paisajes alimentarios rurales carecen de esta oferta, a la vez que el relieve rural de sierras, su población dispersa y su infraestructura de transporte y servicios limitada propiciaría un gasto energético diario mayor al de las áreas urbanas.…”
Section: Discuciónunclassified
“…24 Additionally, only 18.6% of Kansans report eating fruits and vegetables at least 5 times a day. 25 Previous research has identified a need to improve the built food environment through policy changes, 26 as well as addressing higher rates of obesity and physical inactivity among rural residents. 27 Kansas is a predominately rural state.…”
mentioning
confidence: 99%